ROLE OF THE ENGLISH LANGUAGE IN SOCIETY - Rahimova Dilnora, (TADQIQOTLAR, 2026)
Annotation: This article discusses the significant role of the English language in  modern  society.  English  has  become  an  essential  tool  for  communication  in education, science, business, technology, and cultural exchange. The study examines the spread of English and its impact on social development.